Arti Kebangkitan Yesus Menurut Kitab (1 Korintus 15:1-8) - Fidenius Laia; Aprianus Lendrik Moimau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This research is intended to discuss the importance of the resurrection of jesus according to 1 corinthians 15:1-8, by exploring its implications for religious beliefs and practices. Because the theme of the resurrection of Jesus chist is very important and central to the chritian faith. This topic sounds classic, but in reality there are Cristians who rarely report on it because they rarely explore the truth. So, to find its meaning and relevance for believers, the author wants to discuss it theologically through a literature review. This aims to make chistians understand that the theme of the meaning of the resurrection of Jesus christ is the core teaching of the Bible. So that today`s Christians continue to proclaim the risen christ as the center of preaching in the Gospel.